Brand positioning strategy in growing and sustaining South African B2C SMES - Hlatshwayo, Zanele Alice (My University, 2015)
Small to Medium Enterprises (SMEs) have a vital role in both developing and developed economies. This is due to the SMEs’ contribution towards employment and the significant impact these organisations have on the socio-economic development of any country. Specifically in South Africa, SMEs are considered to contribute more than 50% of the current jobs and also contribute between 50% and 60% towards the country’s GDP. Although the figures reflect a positive trend, SMEs are faced with various challenges and a high failure rate. In South Africa, 40% of newly established businesses fail within the first year of business, while 60% fail in their second year and 90% are confirmed failures in the first 10 years of existence. South Africa is considered to be one of the countries with a high SME failure rate. There are various factors that contribute towards this alarming failure rate, including a lack of finance, and/or the lack of management skills. Studies have also shown that a lack of marketing skills and the implementation thereof all contribute towards high failure rates. In terms of marketing, studies have indicated that SME theories and knowledge are under-developed. This is due to the fact that marketing studies and research have concentrated heavily on large corporations compelling SMEs to implement marketing from a large corporation perspective. This is not ideal due to the difference in the scope, the nature of the business and levels of resources. Academics have emphasised the greater need to further contribute towards SME marketing theory. In response to that call, this study examines how brand positioning can be implemented as a marketing framework in growing and sustaining business-to-consumer (B2C) SMEs. The study entailed conducting a literature review on current marketing practices in the quest for recommending a brand positioning strategy relevant to B2C SMEs. This was followed by collecting data through face-to-face interviews with 15 SME B2C owners who represent 15 SME sectors. Following the interrogation of the data it was confirmed that SMEs indeed lack marketing skills. SME marketing practices and tools are not well structured, and marketing guidance is required. Following these findings, brand iii positioning elements in the form of positioning by corporate identity, target user positioning, features and attribute positioning and competitive positioning, formed an SME brand positioning framework that was recommended to develop and sustain B2C SMEs.
Thesis (M.M. (Strategic Marketing))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.